The New Protectionism in Industrial Countries : Beyond the Uruguay Round - Irwin, Douglas (Washington, D.C. : International Monetary Fund, 1994)
This paper presents a broad overview of trade protection in industrial countries from the 1970s to the present. The emphasis of such measures has shifted from the protection of agriculture and basic manufacturing industries, where many industrial countries had lost (or never had) comparative advantage in the 1970s and 1980s, toward the protection and promotion of high-technology sectors in recent years. The new forms of protection--particularly subsidies and antidumping rules--have not necessarily contravened GATT rules, arid the Uruguay Round fell short of reigning in such interventions. While these more recent trade interventions might in principle have an economic justification under certain conditions, theoretical, empirical, and practical considerations call for great skepticism about the desirability and efficacy of such policies. The next challenge for world trade negotiators is to contain the pressures for intervention in these areas. This is a Paper on Policy Analysis and Assessment and the author(s) would welcome any comments on the present text. Citations should refer to a Paper on Policy Analysis and Assessment of the International Monetary Fund, mentioning the author(s) and the date of issuance. The views expressed are those of the author(s) and do not necessarily represent those of the Fund.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet